Konzeptionelle Potenziale des schweizerischen Direktzahlungsregimes fur̈ die EU - Stefan Mann (Agrarwirtschaft: Zeitschrift für Betriebswirtschaft, Marktforschung und Agrarpolitik, 2002)
– What Potentials Does the Swiss Direct Payment Regime Offer for the CAPThe paper has the goal to check whether elements of the Swiss direct payment regime could serve as a model for the EU. It does so by checking the direct payment regime's accordance with the concept of an efficient and sustainable economic policy and by quantitatively examining what impact it has if some of its elements are integrated into the Common Agricultural Policy (CAP). It becomes clear that Swiss agricultural policy roots much firmer in the foundations of public finance theory than the CAP, but that an adaptation in the EU would lead either to large budget increases or to massive income losses for farmers. However, the Swiss example shows that large direct payments can be brought into accordance with public finance theory.
Keywords: 330; Agrarsubvention; Wirkungsanalyse; EU-Agrarpolitik; Umweltpolitik; Schweiz; EU-Staaten